PENGEMBANGAN BACKEND TASHA CROWDFUNDING MENGGUNAKAN METODE ITERATIVE INCREMENTAL - Inayah Dwi Utari; Rahmat Fauzi; Faishal Mufied Al Anshary (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
Micro, small and medium enterprises, or MSMEs are business actors in Indonesia that play a critical role in the absorption of labor and the formation of gross domestic product (GDP). However, their potential is hindered by capital problems. They still rely on capital from banks and personal loans which tend to be tough and also do not guarantee business continuity in the long term. Crowdfunding can be used as an alternative capital. However, there are still many shortcomings of crowdfunding that result in a reluctance to take advantage of it such as being vulnerable to fraud and funds that return not according to the agreement. Based on these problems, developing a Sharia crowdfunding application based on Sharia principles as a capital alternative is needed. This Sharia crowdfunding application requires a backend to run well and optimally. The backend was created using the Laravel framework, incremental iterative methods, and MySQL as a database system. The crowdfunding application was tested using black box testing and user acceptance test. Based on the test results, the crowdfunding application has met user needs in becoming an alternative capital with user acceptance test results of 93.7% for MSMEs, 96.4% for investors, and 92.1% for admins